Prisoner B-3087 - Gratz, Alan, 1972- (Scholastic Press, 2013)
Based on the life of Jack Gruener, this book relates his story of survival from the Nazi occupation of Krakow, when he was eleven, through a succession of concentration camps, to the final liberation of Dachau.